Electrochemical And Radio Frequency Sputtering Growth Of GaN Nanostructures On Porous Silicon - Shamsuddin, Siti Nur Atikah (2019)
This study focuses on the growth and characterization of gallium nitride (GaN) nanostructures deposited on n-type PSi (100) substrate using electrochemical deposition (ECD) and radio frequency (RF) sputtering techniques. In the first step of this work, PSi substrates were obtained using direct current (DC) and pulsed current (PC) electrochemical etching techniques. The result showed that PC etching technique produced higher porosity and more uniform PSi substrate compared to than DC etching technique. In the second step, GaN layer was grown on PSi substrate by ECD technique. The quality of GaN was improved by nitridation process. Several peaks of hexagonal wurtzite (h-GaN) were observed at 32.4⁰, 34.6⁰, and 36.8⁰ which corresponding to the (010), (002), and (101) orientations, respectively